Pengaruh Kualitas Pelayanan dan Digital Marketing Terhadap Loyalitas Pelanggan pada Aplikasi -Wallet (Studi pada Pengguna Dompet Digital di Cimincrang) - Muhammad Raihan Ramadhani; Halimah Zahrah (Indo Publishing, 2026)
This study aims to analyze the effect of service quality and digital marketing on customer loyalty to the DANA e-wallet application in the Cimincrang RW 012 area. This study uses a quantitative approach with a survey method by distributing questionnaires to application users. The results show that service quality has a positive effect on customer loyalty, especially through the aspects of system reliability, transaction security, and service responsiveness. In addition, digital marketing also plays a role in increasing loyalty through digital promotions, intensive communication, and application-based marketing campaigns. Simultaneously, these two variables support each other in shaping e-wallet customer loyalty. This study suggests that e-wallet application managers continue to improve service quality and optimize digital marketing strategies on an ongoing basis in order to strengthen user loyalty amid competition in digital financial services.